Y chromosome haplotypes in Central-South Italy: implication for reference database. - Rapone, C; Geraci, A; Capelli, C; De Meo, A; D'Errico, G; Barni, F; Berti, A; Lago, G (2007)
One hundred and fifty individuals have been sampled across Central-South Italy and genotyped for Y chromosome STRs by PowerPlex Y system. Comparison with previous Italian databases revealed that majority of Y chromosome variation still need to be sampled. Identification of locus duplications, distribution of genetic variation and firstly identified alleles point to the necessity of more focused sampling strategies for reference databases.